2019
DOI: 10.1515/med-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

PYCR1 is associated with papillary renal cell carcinoma progression

Abstract: AbstractObjectiveWe aimed to determine the function of pyrroline-5-carboxylate reductase 1 (PYCR1) on progression of papillary renal cell carcinoma (PRCC) and related mechanism.MethodsThe TCGA database provided us expression profiles of PYCR1 and overall survival rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…In melanoma cells, knockdown of PYCR1 causes decreased activity of the Akt pathway and reduces the expression of RAPTOR, suggesting a downstream inhibition of protein synthesis 96 . Similarly, RNA-interference suppression of PYCR1 decreases levels of activated phospho-Akt and activated phospho-mTOR in renal cancer cells 103 .…”
Section: Proline Biosynthesis and Protein Translationmentioning
confidence: 98%
See 2 more Smart Citations
“…In melanoma cells, knockdown of PYCR1 causes decreased activity of the Akt pathway and reduces the expression of RAPTOR, suggesting a downstream inhibition of protein synthesis 96 . Similarly, RNA-interference suppression of PYCR1 decreases levels of activated phospho-Akt and activated phospho-mTOR in renal cancer cells 103 .…”
Section: Proline Biosynthesis and Protein Translationmentioning
confidence: 98%
“…In some instances, PYCR1 expression is a reliable diagnostic biomarker which predicts poor prognosis in patients with melanoma 96 , breast cancer 64,101 , renal cell cancers 100,103 , and NSCLC 98 . Studies that employed genetic depletion of PYCR1 have confirmed a functional role for PYCR1 in promoting tumor progression and cancer cell survival in colorectal cancer cells 104 , NSCLC cells 42,97,98 , renal cancer cells 64,103 , prostate cancer cells 105 , and IDH1-mutant gliomas 106 .…”
Section: The Ambivalent Role Of Prodh In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…PYCR1 is highly expressed also in prostate cancer tissues (33), in renal cell carcinoma (RCC) (34), in papillary renal cell carcinoma (PRCC) (35) and in human malignant melanoma (MM) (36). These studies showed that PYCR1 expression strongly influence cell behavior (proliferation, colony formation, apoptosis) in different cancer contexts, and correlate with poor outcome and decreased overall survival in patients.…”
Section: Proline Biosynthesis Genes Predict Poor Prognosis In Cancermentioning
confidence: 99%
“…These studies showed that PYCR1 expression strongly influence cell behavior (proliferation, colony formation, apoptosis) in different cancer contexts, and correlate with poor outcome and decreased overall survival in patients. Of particular interest is the finding that PYCR1 ablation inhibits migration and invasion both in PRCC and MM cells, altering phosphorylation of AKT (36) and mTOR (35).…”
Section: Proline Biosynthesis Genes Predict Poor Prognosis In Cancermentioning
confidence: 99%